Impact of Factors Affecting Programme Based Budgeting Performance in Government Organisations in Kenya. - Minjire, Charles N; Ogollah, Dr. Kennedy (Journal of Public Policy and Administration, 2017)
Purpose: The purpose of the study was to establish the factors affecting programme based budgeting performance in public organization in Kenya. Materials and methods: In this study a descriptive survey design was used. Target population include administrators with authority to incur expenditure (AIE Holders), Finance officers, economists, accountants, auditors- internal and external totaling to a population of 247 officers. The researcher used a questionnaire to collect primary data. The SPSS (version 20) computer software aided the analysis. Descriptive statistics was employed to analyze the data. An odd's ratio regression model was applied to determine the relative probability of importance of each factor variable. Results:The study findings indicated that there are adequate policies and procedures guiding PBB budgetary process, stakeholders views and expert opinions are well sought in the development of policies and procedures and the budgetary policies and procedures are not donor forced ideologies but accepted negotiated domestic instrument. Results further indicated that there are adequate laws that make it mandatory for all stakeholders' consultation on budgetary process for the budget to be legitimate, adequate awareness forums and sensitization programmes are undertaken by treasury to sensitize public on budget. Recommendations: The study recommends that the public organizations should ensure that they have effective budget policies and procedure in place and followed to the letter. It is also recommended that firms should invest enough resources to ensure that their objectives and goals are met without constraints. Key words: programme based budgeting, performance, government organisations